ANALISIS KEMAMPUAN SISWA SMPN 2 KOTA TAMBOLAKA DALAM MENYELESAIKAN SOAL FISIKA PADA MATERI HUKUM NEWTON DENGAN MENGGUNAKAN TEORI POLYA - Putri, Yusmiati Inda; Garung, Etheldreda Rosari; Lede, Yulita Adelfin; Kaleka, Yohanis Umbu (JURNAL PEMBELAJARAN FISIKA, 2024)
The research conducted aims to determine the ability of students in solving physics problems using Polya's theory and the difficulties experienced in solving problems. The method used is quantitative with a descriptive approach. The research subjects were 15 students of class VIII SMP Negeri 2 Tambolaka City. Data collection using test instruments in the form of essay questions and interviews to students. The results showed that, the ability of students in solving physics problems was in the high category 26%, moderate 7%, low 47% and very low 20% while aspects of student ability based on Polya's stages are students who understand the problem in the problem 10 students, plan the problem in the problem 9 students, carry out planning in the problem 8 students, look back at the answers in the problem 6 students. Thus the ability of students in grade VIII SMP Negeri 2 Tambolaka city is in the low category in solving physics problems. At the stage of understanding the problem and planning the problem some students have been able to solve it, but at the stage of carrying out the planning and rechecking the answers there are still many students who experience errors in solving it. The difficulties experienced by students are in determining equations, remembering magnitude and units, and calculating complex numbers.